2010
DOI: 10.1097/md.0b013e3181d5dca7
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever and Central Nervous System Involvement

Abstract: We conducted this study to determine familial Mediterranean fever (FMF)-associated central nervous system involvement including demyelinating lesions, stroke, and posterior reversible leukoencephalopathy syndrome (PRES). Patients with MEFV mutations were systematically reviewed through the Medical Biology Unit database. All samples sent for mutation analysis were screened for 10 common MEFV mutations. Patients with FMF and neurologic disorders according to the clinical records were invited for reevaluation. Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…Compared to their spouses, conceivably exposed to the same environmental hazards, FMF patients had similar rate of atherosclerotic CV disease. On the other hand and as mentioned above, ischemic stroke in FMF patients younger than 50 year old was reported by Kalyoncu et al to be more common than expected in age-adjusted general population (0.2 % vs. 0.005-0.01 %) [ 45 ]. Our experience with FMF patients, who suffered ischemic stroke/transient ischemic attack (TIA), was comparable [ 25 ].…”
supporting
confidence: 65%
“…Compared to their spouses, conceivably exposed to the same environmental hazards, FMF patients had similar rate of atherosclerotic CV disease. On the other hand and as mentioned above, ischemic stroke in FMF patients younger than 50 year old was reported by Kalyoncu et al to be more common than expected in age-adjusted general population (0.2 % vs. 0.005-0.01 %) [ 45 ]. Our experience with FMF patients, who suffered ischemic stroke/transient ischemic attack (TIA), was comparable [ 25 ].…”
supporting
confidence: 65%
“…Of these 13 patients, 10 had headaches during acute episodes of the fever, two had convulsions, and another patient had aseptic meningitis. Kalyoncu et al 2 reported 18 patients with neurological signs and detected seven patients with demyelinating lesions, seven patients with cerebrovascular disease, and four patients with reversible posterior leukoencephalopathy syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological involvement in FMF is rare and shows a wide spectrum, including optic neuritis, recurrent aseptic meningitis, cranial nerve lesions, IIH, ischemic stroke due to coincidental reasons, and subclinical visual evoked potentials abnormalities with demyelinating lesions. 2,3 Only a few reliable reports are present on the association of FMF and IIH in adults. 4,5 To our knowledge, there is no report involving children.…”
mentioning
confidence: 99%
“…Especially in adulthood cohort studies suggest that multiple sclerosis [ 40 -42 ], cerebrovascular events [ 43 ], and posterior reversible leukoencephalopathy syndrome (PRES) [ 43 ] are associated with FMF. One report describes the occurrence of headache, convulsions, and aseptic meningitis in children with FMF [ 40 ].…”
Section: Neurological Symptomsmentioning
confidence: 99%